Researching antiseptic properties of shungite when producing red beet juice - Melnyk, Lyudmila; Melnyk (Tkachuk), Nataliia; Melnyk, Zinoviy (My University, 2012)
Іnvestigated antiseptic properties Shung in the production of table beet juice. The efficiency of absorption of harmful microorganisms from juice Shung.
Keywords: zhungite; red beet juice; adsorption; technology; bacteria; yeast; fungi; шунгіт; сік столового буряка; адсорбція; технологія; бактерії; дріжджі; гриби; шунгит; кафедра процесів і апаратів харчових виробництв; кафедра теплоенергетики та холодильної техніки